The kinetics of TEM1 antibiotic degrading enzymes that are displayed on Ure2 protein nanofibrils in a flow reactor. - Benjamin Schmuck; Mats Sandgren; Torleif Härd (PLoS ONE, 2018)
Enzymatic functionalization of cross-β structured protein nanofibrils has hitherto resulted in a severe reduction of the catalytic efficiency of high turnover biocatalysts. It has been speculated that steric restrictions and mass transport pose limits on the attached enzymes, but detailed kinetics analyzing this have not yet been reported. For a more comprehensive understanding, we studied protein nanofibrils endowed with TEM1, a β-lactamase from Escherichia coli. The packing density of TEM1 along the fibrils was controlled by co-fibrillation; in other words, the N-terminal ureidosuccinate transporter Ure2(1-80) from Saccharomyces cerevisiae was simultaneously aggregated with the chimeric proteins TEM1-Ure2(1-80). The mature fibrils were trapped in a column, and the rate of ampicillin hydrolysis was recorded using a continuous substrate flow. The turnover rate was plotted as a function of substrate molecules available per enzyme per second, which demonstrated that an elevated substrate availability counteracts mass transport limitations. To analyze this data set, we derived a kinetic model, which makes it possible to easily characterize and compare enzymes packed in columns. The functional TEM1 nanofibrils possess 80% of the catalytic turnover rate compared to free TEM1 in solution. Altogether, we have created protein nanofibrils that can effectively hydrolyze β-lactam antibiotic contaminations and provided a groundwork strategy for other highly functional enzymatic nanofibrils.